Nonsurgical Chin and Prejowl Modification - Melley, Lauren E.; Altman, Allison; Bloom, Jason D. (Facial Plastic Surgery, 2025)
The chin and prejowl areas play a critical role in the perception of facial harmony. This paper explores nonsurgical approaches for chin and prejowl rejuvenation, emphasizing anatomy, aesthetic concerns, and the plethora of available treatment modalities.Bony landmarks such as the pogonion, menton, and mental protuberance define the chin, while muscles like the mentalis, depressor anguli oris (DAO), and depressor labii inferioris (DLI) influence facial expression and rhytid development. Aging induces volume loss, tissue laxity, and bony absorption, leading to the formation of the prejowl sulcus and reduced jawline definition.Injectable fillers and biostimulators such as hyaluronic acid, calcium hydroxylapatite, and poly-L-lactic acid address volume loss, enhance contours, correct chin underprojection, and fill both deep and superficial rhytids. Neuromodulators like botulinum toxin reduce muscle hyperactivity to smooth dynamic wrinkles. Energy-based modalities, including radiofrequency, ultrasound, and laser, offer options for skin tightening, fat reduction, and improving skin texture.The paper highlights the benefits and limitations of nonsurgical techniques available to treat the chin and prejowl, emphasizing the need for anatomical precision to optimize safety and efficacy. Although nonsurgical treatments cannot replace surgical interventions, they often provide effective, temporary solutions for patients seeking low-downtime alternatives.
Keywords: chin; prejowl; minimally invasive; rejuvenation; injectables